Association between interpersonal relationships and depression among children living in Tehran`s shelters - Ahangar, Katayoon; Mansor, Mariani; Juhari , Rumaya (Islamic Azad University,Garmsar Branch, 2013)
The purpose of this paper was to examine the correlation between interpersonal relationship and depression among children living in Tehran’s shelters. A correlational design was employed in this study and convenience sampling method was used to select respondents. A total number of 162 Iranian children, including 101 males and 61 females between the ages 7 to 15 years old, from 9 governmental shelters in Tehran were included in this research. The results revealed a negative significant correlation between various interpersonal relationship and depression. No significant difference in depression among male and female respondents. Two kinds of interpersonal relationship variables namely, relationship with roommates and guardians were potentially related to the depression after controlling for other variables.